The equation is: 27.46 = 1.95x + 2.50
The answer is 12.8
Answer:
![\large\boxed{(s-2)(s+2)(s-3)=(s^2-4)(s-3)=s^3-3s^2-4s+12}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%28s-2%29%28s%2B2%29%28s-3%29%3D%28s%5E2-4%29%28s-3%29%3Ds%5E3-3s%5E2-4s%2B12%7D)
Step-by-step explanation:
![s^2-4=s^2-2^2=(s-2)(s+2)\\\\\text{used}\ a^2-b^2=(a-b)(a+b)\\\\s^2-5s+6=s^2-2s-3s+6=s(s-2)-3(s-2)=(s-2)(s-3)\\\\\text{Therefore}\ LCD(s^2-4,\ s^2-5s+6)=(s-2)(s+2)(s-3)](https://tex.z-dn.net/?f=s%5E2-4%3Ds%5E2-2%5E2%3D%28s-2%29%28s%2B2%29%5C%5C%5C%5C%5Ctext%7Bused%7D%5C%20a%5E2-b%5E2%3D%28a-b%29%28a%2Bb%29%5C%5C%5C%5Cs%5E2-5s%2B6%3Ds%5E2-2s-3s%2B6%3Ds%28s-2%29-3%28s-2%29%3D%28s-2%29%28s-3%29%5C%5C%5C%5C%5Ctext%7BTherefore%7D%5C%20LCD%28s%5E2-4%2C%5C%20s%5E2-5s%2B6%29%3D%28s-2%29%28s%2B2%29%28s-3%29)
A) The degree of the first term is... 1
![first \ term = 3t](https://tex.z-dn.net/?f=first%20%5C%20term%20%3D%203t%20)
The degree of the second term is... 2
![second \ term = t^2](https://tex.z-dn.net/?f=second%20%5C%20term%20%3D%20t%5E2)
The degree of the third term is... 4
![third \ term = t^4](https://tex.z-dn.net/?f=third%20%5C%20term%20%3D%20t%5E4)
b) The leading term of the polynomial is... 7t⁴
The leading coefficient of the polynomial is... 7
c) The degree of the polynomial is... 4
So in order to get rid of the cubed roots, you must cube each side of the equation. what you do to one side you do to the other at all times. so when you cube a cubed root, you get whats in side. so after the first step, you should get x+5=8(2x+6) now distribute the 8 on the right side of the equation and get x+5=16x+48solve for x and get x=-43/15
In an equation using x is just a place holder because those numbers are variables so it doesn't matter whether it is x or w.